Legal Principles and Methodological Approaches to Organizing Pre-Trial Investigation of Environmental Criminal Offenses - Romaniuk, Myroslav; Lypnytska, Yevheniia; Demianchuk, Tetiana; Herasymenko, Oleksadr; Husak, Andrii P. (Grassroots Institute, 2025)
The increase of environmental crime, instigating/provoking or affecting critical infrastructure, has immediate imperative law enforcement, legal, procedural, and forensic standpoints. At the same time, existing pre-trial investigation GIS is still highly decentralized, fragmented, reactive, and lacks specialization and cross-sector coordination. This research work aims to conceive an underlying legal and procedural framework for the effective investigation of environmental infrastructural crime, mainly focusing on crimes against common goods. This research applies a legal-forensic matrix model (i.e., theoretical framework), time efficiency indexing, and comparative scenario simulation. The study was based on an examination of 300 pre-trial cases from eight European jurisdictions, including systems in transition. More generally, the results support an association between greater procedural integration and improved procedure as well as evidentiary outcomes; across all jurisdictions, Germany and the Netherlands were among those with the strongest record on both compliance with Soviet standards of HDPE ordering procedures and exceptional case thresholds. In addition, the study introduces two novel assessment tools: the Legal-Forensic Matrix, and the Time Efficiency Index. These results highlight the importance of strengthening digital capabilities and specialized training, plus harmonized protocols for response, especially to harmful crimes against ecosystems and strategic infrastructure. The novelty of the research article is a merger between legal procedural analysis and forensic performance metrics in an environmental investigation. Subsequent research should centre on AImediated pre-trial diagnosis, dynamic legal algorithm design, and the evaluation of judicial outcomes in order to resolve the discrepancy between environmental risks and criminal responsibility.
Keywords: Environmental crime investigation; Legal-forensic matrix; Pre-trial procedures; Evidentiary admissibility; Green criminal law